Prevalência e fatores associados aos acidentes viários automobilísticos com lesão corporal entre adultos no Nordeste brasileiro: achados da pesquisa nacional de saúde de 2013 - Lima, Tamires Feitosa de (2020)
Introduction: A car accident is a traffic accident involving a four-wheel vehicle that carries a maximum of ten people, including the driver. Automobile accidents have multifactorial causes and generate individual and collective damages in addition to significant socioeconomic factors. Objective: To estimate the prevalence and factors associated with motor vehicle accidents (AVA) with bodily injury in the adult population of northeastern Brazil, in 2013. Methods: Sectional study, based on data from the National Health Survey (PNS) in 2013 , being considered 93 records that include only reports of AVA with bodily injury. They were analyzed as variables selected by the AVA; personal characteristics; personal health history; and practices, attitudes and practices in relation to the use of automobiles. The database was standardized and analyzed using SPSS® version 20 software. Prevalence and 95% confidence intervals (95% CI) were calculated. For association analysis in contingency tables, Pearson's square was used. Results: In the Northeast, 93 people (14.3%) self-reported AVA with bodily injuries. One region has the lowest rate (14.3%) in relation to other regions. Among the VLEs, 25.6% occur at work, 21.1% at work, 22.6% of the victims of carrying out their usual activities, 27.3% need medical assistance, 2.2% need hospitalization for 24 hours or more and 9.3% had / have some sequence. The individuals who most self-reported AVA with bodily injuries are predominantly men (59.9%), under 40 years old (67.5%), brown or black (66.2%), single (50.2%), that studied information (95.2%), with higher education than primary education / EJA (98.9%), who drive cars (70.8%), using this means of transport (76.7%), use the belt safety both in the back seat (44.9%) and in the front (79.8%). However, he consumes alcoholic beverages once a month or more (43.8%). Most use weekly (83.9%), one or more doses of alcoholic beverage (99%), but do not consume before driving (85.9%), but experience medium / severe difficulty in vision (both -24, 2%, how close - 12.5%). The factors associated with the injured VLE were found, separated, legally divorced, divorced (OR = 2.45; CI = 0.95-6.35), with higher education than the former primary / EJA (p = 0.00; OR = 10.7; CI = 2.45 - 46.59), without sleep problems (p = 0.02; OR = 2.05; CI = 1.12 - 3, 81), without hearing impairment (p = 0.02; OR = 4.98; CI = 1.04 - 23.82), but with the need for resources to aid vision (p = 0.00; OR = 3, 0; CI = 1.70 - 5.29), difficulty in seeing far away (p = 0.03; OR = 2.1; CI = 1.05 - 4.3), being car drivers (p = 0 , 00; OR = 4.75; CI = 2.51 - 8.97), and frequently used by car (p = 0.00; OR = 10.3; CI = 4.75 - 23.67) , reported not consuming alcohol before driving (p = 0.02; OR = 5.02; CI = 1.66 - 15.17), but when drinking alcohol or taking one or more doses (p = 0.00; OR = 12.9; CI = 2.6 - 63.4). Conclusion: The Northeast region has the lowest prevalence of VLE in Brazil, but has the 3rd highest absolute number of self-reported cases. They are associated with AVA: married and widowed marital status, separated, legally divorced, divorced, attending courses higher than the old primary / EJA, having no sleep problems, having no or slight degree of hearing impairment, using some type of resource to see, having medium / severe difficulty or not seeing from a distance, driving a car, always or almost always using a car as a means of transport, not consuming alcohol before driving and not being a smoker. It warns about the need for intersectoral networking to strengthen, improve and direct traffic safety strategies in order to reduce injuries, disabilities and mortality from AVA.